1993
DOI: 10.1017/s002211209300031x
|View full text |Cite
|
Sign up to set email alerts
|

Vorticity measurements in the near wake of a circular cylinder at low Reynolds numbers

Abstract: The technique of the particle streak method has been applied to the study of bluff-body wakes at low Reynolds number. Vorticity and shear stress were measured to an accuracy of 15–20%. The vortex shedding cycles at Reynolds number of 73 and 226 are shown and the differences between the two are highlighted. Quantitative descriptions of the previously described vortex splitting phenomenon in the near wake are made, which leads to a description of the vortex shedding mechanism at low Reynolds number. The definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 10 publications
10
37
1
Order By: Relevance
“…The results are therefore complementary to the ones published by Green and Gerrard (1993) who explained the vortex shedding process for Ri D ¼ 0. In the second part of the result section, the flow close around the cylinder will be discussed.…”
Section: Resultssupporting
confidence: 83%
“…The results are therefore complementary to the ones published by Green and Gerrard (1993) who explained the vortex shedding process for Ri D ¼ 0. In the second part of the result section, the flow close around the cylinder will be discussed.…”
Section: Resultssupporting
confidence: 83%
“…In the higher-Re regime (Re = 400-600) the shed-vortex cores rapidly cross the centeraxis. The change observed here in the near-wake behaviour is similar to that described by Green and Gerrard (1993) for the circular cylinder in the fully established regime. It has been shown to be linked with the evolution of the shear-stress field.…”
Section: Wake-flow Structure In the Mid-cross Planesupporting
confidence: 87%
“…A lot of effort was made to explain the physics of circular cylinder wake dynamics. [1][2][3] They showed that vortex shedding for low Reynolds numbers can be characterized by vortex splitting and high shear stress occurring in the near-wake. Unal and Rockwell 4 investigated the near wake vortex formation from the context of absolute instability and showed that the shear layer separating from the cylinder shows an exponential variation of fluctuating kinetic energy with distance downstream of the cylinder.…”
Section: Introductionmentioning
confidence: 99%